Role of TRAFs in Signaling Pathways Controlling T Follicular Helper Cell Differentiation and T Cell-Dependent Antibody Responses - Pedros, Christophe; Altman, Amnon; Kong, Kok-Fai (Frontiers in Immunology, 2018)
Follicular helper T (TFH) cells represent a highly specialized CD4+ T cell subpopulation that supports the generation of germinal centers (GC) and provides B cells with critical signals promoting antibody class switching, generation of high affinity antibodies and memory formation. TFH cells are characterized by the expression of the chemokine receptor CXCR5, the transcription factor Bcl-6, costimulatory molecules ICOS and PD-1, and the production of cytokine IL-21. The acquisition of a TFH phenotype is a complex and multistep process that involves signals received through engagement of the TCR along with a multitude of costimulatory molecules and cytokines receptors. Members of the Tumor necrosis factor Receptor Associated Factors (TRAF) represent one of the major classes of signaling mediators involved in the differentiation and functions of TFH cells. TRAF molecules are the canonical adaptor molecules that physically interact with members of the Tumor Necrosis Factor Receptor Superfamily (TNFRSF) and actively modulate their downstream signaling cascades through their adaptor function and/or E3 ubiquitin ligase activity. OX-40, GITR, and 4-1BB are the TRAF-dependent TNFRSF members that have been implicated in the differentiation and functions of TFH cells. On the other hand, emerging data demonstrate that TRAF proteins also participate in signaling from the TCR and CD28, which deliver critical signals leading to the differentiation of TFH cells. More intriguingly, we recently showed that the cytoplasmic tail of ICOS contains a conserved TANK-binding kinase 1 (TBK1)-binding motif that is shared with TBK1-binding TRAF proteins. The presence of this TRAF-mimicking signaling module downstream of ICOS is required to mediate the maturation step during TFH differentiation. In addition, JAK-STAT pathways emanating from IL-2, IL-6, IL-21, and IL-27 cytokine receptors affect TFH development, and crosstalk between TRAF-mediated pathways and the JAK-STAT pathways can contribute to generate integrated signals required to drive and sustain TFH differentiation. In this review, we will introduce the molecular interactions and the major signaling pathways controlling the differentiation of TFH cells. In each case, we will highlight the contributions of TRAF proteins to these signaling pathways. Finally, we will discuss the role of individual TRAF proteins in the regulation of T cell-dependent humoral responses.